2012
DOI: 10.1590/s0365-05962012000600024
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for hidradenitis suppurativa: a pilot study

Abstract: The hidradenitis suppurativa is a chronic debilitating inflammatory disease whose etiology is not fully understood. We conducted a pilot case-control study matched by sex and age with other dermatological patients to analyze possible risk factors associated with this disease. We included 15 cases and 45 controls, 67% were women. Bivariate and multivariate logistic regression analysis identified significant association with smoking, higher body mass index and family history. The use of hormonal contraceptives w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 8 publications
2
20
0
1
Order By: Relevance
“…Patients with HS were younger, and more likely to be black, uninsured and admitted during the autumn and summer months. We observed higher rates of HS in female inpatients, which appears to be consistent with previous findings that women are more likely to have HS, especially during puberty when the secretory activity of apocrine glands is increased . A previous retrospective cohort study found the incidence of HS to be higher in female patients, particularly younger female patients and in African Americans .…”
Section: Discussionsupporting
confidence: 91%
“…Patients with HS were younger, and more likely to be black, uninsured and admitted during the autumn and summer months. We observed higher rates of HS in female inpatients, which appears to be consistent with previous findings that women are more likely to have HS, especially during puberty when the secretory activity of apocrine glands is increased . A previous retrospective cohort study found the incidence of HS to be higher in female patients, particularly younger female patients and in African Americans .…”
Section: Discussionsupporting
confidence: 91%
“…Brazilian HS subjects were mainly adults between third and fourth decades, which corroborate the results of two previous hospital‐based Brazilian studies . The prevalence of the disease increases after puberty, according to apocrine glands maturity.…”
Section: Prevalence Of Hidradenitis Suppurativa According To Dermatolsupporting
confidence: 88%
“…Hidradenitis suppurativa (HS) is a chronic and relapsing follicular autoinflammatory disorder that inflicts major impact in quality of life . Population prevalence studies of HS are scarce, especially in Latin America …”
Section: Prevalence Of Hidradenitis Suppurativa According To Dermatolmentioning
confidence: 99%
“…After evaluation of the abstract and when necessary, the full text, nine studies were found to be eligible for inclusion in this systematic review (Fig. ) . General characteristics of the eligible studies included are presented in Table .…”
Section: Resultsmentioning
confidence: 99%